Building socialism and communism: Planning and the process of transcending markets - Al Campbell (The University of Utah, Department of Economics, 2008)
This short paper will argue the following 8 points. This paper will - 1) as a background to what this paper will consider, accept both that planning is an inherent and essential aspect of socialism, and that not only the details but the very basic nature of the planning that will be appropriate in today's world for supporting (various) transitions to socialism has to be created; 2) focus on just one of many questions that need to be resolved concerning the appropriate basic structure of today's socialist planning, the question of the role of markets in planning for socialism; 3) discuss the essential nature of capitalist markets in relation to shaping their participants in ways appropriate for capitalism (any mode of production creates its own presuppositions), and therefore in ways inappropriate for either living under socialism or effecting the transition from capitalism to socialism ; 4) review Marx and Engels' position that immediately after the seizure of power by a workers' government capitalist commodity production and capitalist markets will still exist; 5) review Marx and Engels' position that the transition to socialism will involve a withering away of both capitalist markets and commodity production, and that under socialism these will already both be transcended; 6) then argue, closely based on Marx and Engels' writings, that under socialism there will necessarily be markets, albeit markets of a different nature that I will call socialist markets (and I will carefully indicate their fundamental difference from capitalist markets); 7) then argue that notwithstanding that socialist markets are both necessary for socialism and different from capitalist markets, they will still represent barriers to the transition from socialism to communism; 8) finally discuss what will be necessary for the transcendence of socialist markets which is a necessity for completing the transition to a communist mode of production, which Marx indeed saw as a society without markets.
Keywords: 330